2002
DOI: 10.1080/09553000110117818
|View full text |Cite
|
Sign up to set email alerts
|

Antibody and radionuclide characteristics and the enhancement of the effectiveness of radioimmunotherapy by selective dose delivery to radiosensitive areas of tumour

Abstract: The extent of heterogeneity of dose deposition in tumour is highly dependent on the antibody characteristics and radionuclide properties, and can enhance therapeutic efficacy through the selective dose delivery to the radiosensitive areas of tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…Monovalent antibodies have faster circulatory clearance and weaker antigen binding than IgGs, resulting in lower tumor uptake and therapeutic potential but reduced systemic toxicity. It has also been suggested that they have the ability to localize more rapidly into tumor deposits (37,38). However, our results show that there was no physical barrier to localization and penetration of IgG (MW 150 kDa) into and through hepatic tumor deposits of all sizes.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Monovalent antibodies have faster circulatory clearance and weaker antigen binding than IgGs, resulting in lower tumor uptake and therapeutic potential but reduced systemic toxicity. It has also been suggested that they have the ability to localize more rapidly into tumor deposits (37,38). However, our results show that there was no physical barrier to localization and penetration of IgG (MW 150 kDa) into and through hepatic tumor deposits of all sizes.…”
Section: Discussioncontrasting
confidence: 50%
“…Indeed, some a particles and low-energy h particles may be more suitable for tackling small tumor deposits and adjuvant disease. We have previously used phosphor images of radioantibody localization to model dose distribution for a range of isotopes (18,19,37). However, the novel microscopy in the current study has provided a far more accurate picture of antibody distribution in relation to tumor microenvironment and will now inform models of energy deposition for antibody-bound radionuclides to determine optimal pairings of antibody and radionuclide for different situations.…”
Section: Discussionmentioning
confidence: 95%
“…Data from the current and previous studies (10,42) indicate similar localization of fluorescently and radiolabeled A5B7, and suggest that dose deposition from 131 I will treat most of the SW1222 tumor, but leave regions of LS174T untreated. Future studies will use the high-resolution images of antibody distribution for more accurate dosimetry modeling of therapeutic radionuclides, including dose to normoxic and hypoxic regions of viable tumor.…”
Section: Discussionmentioning
confidence: 72%
“…In previous articles, we have discussed how properties related to the antibody and radionuclide effect on therapeutic outcome, and how these may be optimized for therapy (8)(9)(10)(11). We have also shown that radioimmunotherapy can significantly enhance other therapies such as vascular-disrupting agents without increasing toxicity (12)(13)(14), and this is currently in clinical trial within our department.…”
Section: Introductionmentioning
confidence: 99%
“…2a). Antibodies localize most efficiently in the periphery of the tumor [9]; this provides a therapeutic advantage, because the targeted therapy is fre- Fig. 1.…”
Section: Tumor Pathophysiology and Targetsmentioning
confidence: 99%